Payment Methods in Acquisitions : A Study on Short-Term Performance of Indian Non - Financial Acquiring Firms - Bijay Sankar, B. P.; Leepsa, N. M. (Indian Journal of Research in Capital Markets, 2018)
The present study examined the short-term stock performance of acquirers due to the announcement of different payment methods in mergers and acquisitions (M&A) deals. The investigation explored if there were any significant changes in the abnormal returns (AR) of acquiring companies as they chose different payment methods. Event study methodology was used to investigate the acquirers' AR due to the announcement of three types of payment methods, that is, cash, stock, and mixed in M&A deals during the period from April 1, 2000 to March 31, 2017. The analysis was carried out by taking 197 cash deals, 138 stock deals, and 39 mixed payment methods deals which were announced by Indian acquiring companies from the non-financial sector. Abnormal returns were calculated for a period of 61 days surrounding the event announcement day applying the market model. The parametric test t - statistic, Patell Z test, and a non-parametric test (sign test) were used to check the robustness of the results. The findings indicated that the payment method used in M&A deals was a vital factor in explaining stock returns during the announcement period. The results specified that the acquirer from non-financial sector gained positively higher ARs in the pre-announcement period for cash and mixed payment methods deals than stock payment method. The results also showed that the stock payment method deals generated negative returns in various event window periods across the announcement day. The information gained from this study will help the investors generate more short-term profit from the Indian stock market.